THE MANTLE OF THE SHOP STEWARD IS NOT AN EASY ONE TO WEAR NUMSA obo Motloba v Johnson Control Automotive SA (Pty) Ltd (2017) 38 ILJ 1626 (LAC) Revisited - Tumo Charles Maloka; Reginald Matsheta (Obiter, 2023)
NUMSA obo Motloba v Johnson Controls Automotive SA (Pty) Ltd (2017) 38 ILJ 1626 (LAC) (Motloba) raises four discrete, yet interrelated issues that require close examination. The first relates to the constitutional and statutory protection accorded to trade union membership and activities. The second engages the exercise of organisational rights in the workplace. With the demise of the duty to bargain, created to breathe life into collective bargaining and provide the lifeblood to recognised trade unions in the workplace. The third brings to the surface the recurrent headache for management concerning the dual and contradictory role of the shop stewards on the shop floor. The point of immediate relevance is that, while conducting union activities, a shop steward in theory, at least, operates on equal footing with management. It merits emphasising that the theory becomes murky when the union official is also an employee. (Re Workers’ Compensation Board and Workers’ Compensation Board Employees Union (1990) 15 LAC (4th) 332, 335). Put simply, “the ordinary rules applicable to the normal employer-employee relationship are then somewhat relaxed” (FAWU v Haverstime Corporation (Pty) Ltd [2007] BLLR 638 (LC) par 42 (Haverstime)). Be that as it may, a shop steward is still an employee of a company with the usual obligation to conform to all workplace rules. Fourth, and possibly most important, shop stewards’ propensity for an “anything goes approach” in their dealing with management. The contentious issue encountered here concerns the tendency of shop stewards to exceed the bounds of acceptable conduct in fulfilling their representational responsibilities. As a result, trade union representatives have been disciplined and in extreme cases dismissed for misconduct. Accordingly, the marginal line separating insubordination and insolence, the interconnected acts of intimidation and assault, disruptive conduct in the course of collective bargaining process, misconduct at disciplinary or arbitration proceedings as well as the breakdown of the trust relationship and intolerability occasioned by dishonesty deserve critical scrutiny.